1945
DOI: 10.1063/1.1707615
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Certain Muscle Fibrils as Revealed by the Use of Electron Stains

Abstract: Fibrils from certain molluscan muscles, in particular the adductor muscles of the clam Venus mercenaria, were examined with the electron microscope and found to possess periodic variations in structure. In order to make these structural variations visible, it was necessary to treat the fibrils with reagents of high electron scattering power (electron stains). Phosphotungstic acid was found to be particularly suitable. This stain combines with specific regions in the fibrils, forming a remarkably regular geomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

1953
1953
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(25 citation statements)
references
References 10 publications
1
24
0
Order By: Relevance
“…The structural characteristics of paramyosin containing thick filaments are the filament (or sometimes just its core) possessing one or more of 1) a prominent 14.5 nm periodicity (amphioxus: Flood et al, 1969;Yongshui and Zuxun, 1979;mollusc: Elliott et al, 1957;Philpott et al, 1960;Ishii and Takahashi, 1983), 2) a ribbon-like structure (Nematomorpha: Lanzavecchia et al, 1977), 3) long, typically 72 nm, periodicity, sometimes with a multiple of 14.5 nm substructure (Echinodermata: Baccetti and Rosati, 1968;annelid: Lanzavecchia, 1972;Camatini et al, 1976;Nematomorpha: Swanson, 1971b;Lanzavecchia et al, 1977;Deitiker and Epstein, 1993;Epstein et al, 1995;mollusc: Bear, 1944;Jakus et al, 1944;Hall et al, 1945;Schmitt et al, 1947;Bear and Selby, 1956;Hanson et al, 1957;Hodge, 1959;Kahn and Johnson, 1960;Elliott, 1964bElliott, , 1968bSobieszek, 1973;Heumann, 1973;Eshleman et al, 1982), or 4) a checkerboard pattern (a 'Bear-Selby net') with a repeat distance typically of 5 × 14.5 = 72 nm (Fig. 3A) (mollusc: Lanzavecchia, 1966Lanzavecchia, , 1972Szent-Györgyi et al, 1971;Heumann, 1973;Nonomura, 1974;Elliott, 1979;Castellani et al, 1983;Ishii and Takahashi, 1983;Bennett and Elliott, 1984;Panté, 1994;…”
Section: 21mentioning
confidence: 99%
See 1 more Smart Citation
“…The structural characteristics of paramyosin containing thick filaments are the filament (or sometimes just its core) possessing one or more of 1) a prominent 14.5 nm periodicity (amphioxus: Flood et al, 1969;Yongshui and Zuxun, 1979;mollusc: Elliott et al, 1957;Philpott et al, 1960;Ishii and Takahashi, 1983), 2) a ribbon-like structure (Nematomorpha: Lanzavecchia et al, 1977), 3) long, typically 72 nm, periodicity, sometimes with a multiple of 14.5 nm substructure (Echinodermata: Baccetti and Rosati, 1968;annelid: Lanzavecchia, 1972;Camatini et al, 1976;Nematomorpha: Swanson, 1971b;Lanzavecchia et al, 1977;Deitiker and Epstein, 1993;Epstein et al, 1995;mollusc: Bear, 1944;Jakus et al, 1944;Hall et al, 1945;Schmitt et al, 1947;Bear and Selby, 1956;Hanson et al, 1957;Hodge, 1959;Kahn and Johnson, 1960;Elliott, 1964bElliott, , 1968bSobieszek, 1973;Heumann, 1973;Eshleman et al, 1982), or 4) a checkerboard pattern (a 'Bear-Selby net') with a repeat distance typically of 5 × 14.5 = 72 nm (Fig. 3A) (mollusc: Lanzavecchia, 1966Lanzavecchia, , 1972Szent-Györgyi et al, 1971;Heumann, 1973;Nonomura, 1974;Elliott, 1979;Castellani et al, 1983;Ishii and Takahashi, 1983;Bennett and Elliott, 1984;Panté, 1994;…”
Section: 21mentioning
confidence: 99%
“…Most early work favored a paracrystalline or stacked flat layer (ribbon) structure (Hall et al, 1945;Bear and Selby, 1956;Elliott et al, 1957;Elliott and Lowy, 1961;Elliott, 1964a;Lanzavecchia, 1966). This was followed by a period in which helical properties were believed to be present in large diameter thick filaments (Elliott and Lowy, 1969;Elliott, 1971), giving rise to models in which the paramyosin dimers were arranged to form a sheet that was then either rolled up like a rug to form the paramyosin filament (Elliott and Lowy, 1970;Lanzavecchia, 1977), or the filament was composed of concentrically nested cylinders of paramyosin sheets (Heumann, 1980).…”
Section: 21mentioning
confidence: 99%
“…Clearly, if the stain contains heavy atoms, fewer molecules are required to cause a given increase in density. Early work by Hall (17) and Hall et al (18) suggested the use of heavy metal ions as electron stains.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphotungstic acid (PTA) has long been used as a protein precipitant (19), and Hall et al (9,10) introduced it for positive staining of whole muscle and collagen fibrils. From these and other studies (5-7, 11-13, 18), it was concluded that PTA acted as an anionic stain for the positively charged groups of protein.…”
Section: Introductionmentioning
confidence: 99%